The possible effects of the magnetic declination on the wave polarisation coefficients at the cutoff point -: Abstract - Aydogdu, M; Özcan, O (Vsp Bv, 2000)
The dispersion relation and the wave polarisation coefficients of the electromagnetic waves in the ionospheric plasma have been obtained by considering the magnetic declination. If the magnetic declination is taken into account, the polarisation coefficients have red and imaginary parts. It is pointed out that the peculiarity of the real parts of the wave polarisation coefficients become more obvious in the vicinity of the frequency omega(= omega (pe) + omega (pi)) in the ionospheric plasma, while has no effect on the imaginary parts. This result is different from as in the absence of the magnetic declination.